2020
DOI: 10.1186/s12968-020-00663-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of subclinical myocardial dysfunction in cocaine addicts with feature tracking cardiovascular magnetic resonance

Abstract: Background Cocaine is an addictive, sympathomimetic drug with potentially lethal effects. We have previously shown with cardiovascular magnetic resonance (CMR) the presence of cardiovascular involvement in a significant percentage of consecutive asymptomatic cocaine addicts. CMR with feature-tracking analysis (CMR-FT) allows for the quantification of myocardial deformation which may detect preclinical involvement. Therefore, we aimed to assess the effects of cocaine on the left ventricular myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
1
0
4
Order By: Relevance
“…Da amostra de artigos selecionada, 40% deles (n=4) identificaram possíveis riscos de desenvolvimento de doenças cardiovasculares sofridas pelos usuários de cocaína, como arritmias cardíacas (AC), infarto agudo do miocárdio (IAM), angina de peito (AP), morte súbita de origem cardíaca (MSOC), crises hipertensivas (CH), acidente vascular encefálico (AVE) e comprometimento do ventrículo esquerdo (CVE) 9,10,11,12 . Por conseguinte, 1 artigo (10%) atrelou depressão no processamento cognitivo e traços de impulsividade associados ao uso da cocaína 13 .…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Da amostra de artigos selecionada, 40% deles (n=4) identificaram possíveis riscos de desenvolvimento de doenças cardiovasculares sofridas pelos usuários de cocaína, como arritmias cardíacas (AC), infarto agudo do miocárdio (IAM), angina de peito (AP), morte súbita de origem cardíaca (MSOC), crises hipertensivas (CH), acidente vascular encefálico (AVE) e comprometimento do ventrículo esquerdo (CVE) 9,10,11,12 . Por conseguinte, 1 artigo (10%) atrelou depressão no processamento cognitivo e traços de impulsividade associados ao uso da cocaína 13 .…”
Section: Resultsunclassified
“…De acordo com a revisão, os usuários de cocaína, principalmente com sua utilização abusiva, estão sujeitos a manifestações sistêmicas e bucais. As manifestações sistêmicas envolvem, em grande parte, riscos cardiovasculares e ações no SNC, já que a cocaína é considerada uma droga estimulante, bloqueando a receptação de dopamina e noradrenalina na fenda sináptica, o que causa uma estimulação adrenérgica e uma posterior sensação de bem-estar no organismo, sendo esse o motivo do vício 10 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Another study showed high iron deposition in the myocardium to be detectable including CMR-FT-derived RV deformation and therefore timely modification and chelation therapy may be navigated by this non-invasive imaging approach [92]. Subclinical myocardial involvement in the form of both strain impairment and increased dyssynchrony was also detected by CMR-FT analyses in patients with cocaine addiction [93]. Noteworthy, that CMR strain analyses not only enable detection of functional deterioration and adverse influence of substances but also allows monitoring of HF medication like levosimendan and its effects on cardiac function as a commonly administered drug in higher stages of HF [94].…”
Section: Myocardial Inflammation and Other Cardiac Disordersmentioning
confidence: 99%